Steven johnson syndrome induce by carbamazepine in epileptic patient: a case report - Nyoman Yoga Maya Pramita; Prima Saraswati Sanjiwani Sudarsa; Ratih Purnamasari Nukana (Bali Dermatology Venereology and Aesthetic Journal, 2019)
Introduction: Steven Johnson Syndrome (SJS) is life-threatening skin reaction, it is a mucocutaneous disorder induced by immune complex-mediated hypersensitivity reaction. Most frequent offending agents are antibiotic, antiretroviral and aromatic anticonvulsants. Problems arise when these drugs are required for long-term use and necessary for several health conditions. These case series aim to describe SJS and provide replacement therapy especially inpatient with epilepsy. Case report: A 37 years old female was consulted from neurology department with chief complaints an erythematous rash on her chest, back upper and lower extremities accompanied with fever, the patient also complaint erosions on her lips. She had history of seizure and was prescribe Carbamazepine. Carbamazepine was replaced and patient treated with dexamethasone intravenously. After 1 week of admitted there is an improvement. Conclusion: Steven Johnson Syndrome (SJS) is a life-threatening disease, the replacement of the suspected drugs and appropriate therapy can improve the prognosis of patient.